Preventing and debunking earthquake misinformation: Insights into EMSC's practices - Fallou, Laure; Corradini, Marina; Bossu, Rémy; Cheny, Jean-Marc (Frontiers in Communication, 2022)
Misinformation spreads fast in times of crises, corroding public trust and causing further harm to already vulnerable communities. In earthquake seismology, the most common misinformation and misleading popular beliefs generally relate to earthquake prediction, earthquake genesis, and potential causal relations between climate, weather and earthquake occurrence. As a public earthquake information and dissemination centre, the Euro-Mediterranean Seismological Centre (EMSC) has been confronted with this issue over the years. In this paper we describe several types of earthquake misinformation the EMSC had to deal with during the 2018 Mayotte earthquake crisis and the 2021 La Palma seismic swarm. We present frequent misinformation topics such as earthquake predictions received via our channels. Finally, we expose how, based on desk studies and users’ surveys, the EMSC progressively improved its communication strategy and tools to fight earthquake misinformation and restore trust in science.